2008
DOI: 10.1097/mbc.0b013e3282f2b5d9
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with antithrombin III therapy to prevent progression of hepatic venoocclusive disease

Abstract: Venoocclusive disease (VOD) is the most frequent cause of early nonrelapse mortality among patients receiving high-dose chemoradiotherapy and hematopoietic stem cell transplantation. Endothelial injury of sinusoids and hepatic veins following chemotherapy is considered the initial event in the development of VOD. Activation of the coagulation cascade and inflammatory processes following endothelial injury results in a hypercoagulable state and a localized consumption of the natural anticoagulants, antithrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Anti‐thrombin has been investigated in a number of small studies as levels of anti‐thrombin are low in patients with VOD and anti‐thrombin has a protective effect on the vascular endothelium (Morris et al , ; Mertens et al , ). Peres et al () reported a retrospective review of 48 patients with VOD who received early treatment with anti‐thrombin. The overall 100‐d mortality was 17% (10% in the mild/moderate group, 39% in the severe group).…”
Section: Prevention Of Vodmentioning
confidence: 99%
“…Anti‐thrombin has been investigated in a number of small studies as levels of anti‐thrombin are low in patients with VOD and anti‐thrombin has a protective effect on the vascular endothelium (Morris et al , ; Mertens et al , ). Peres et al () reported a retrospective review of 48 patients with VOD who received early treatment with anti‐thrombin. The overall 100‐d mortality was 17% (10% in the mild/moderate group, 39% in the severe group).…”
Section: Prevention Of Vodmentioning
confidence: 99%
“…One such agent, antithrombin III, was examined in a retrospective review of 48 patients (adults and children) who received the agent as treatment of VOD following SCT, yielding an overall 100-day mortality of 17%. The fatality rates in patients who developed mild/moderate and severe VOD were 9 and 38%, respectively [77]. A prospective study was then performed to compare the incidence of VOD in 71 children undergoing SCT who did not receive any specific VOD prophylaxis or therapy, with 91 children who received antithrombin III prophylaxis [68].…”
Section: Combination Therapy With Defibrotide In Childrenmentioning
confidence: 99%
“…Previously, fibrinolytic treatment was the preferred approach, with or without anticoagulants, but the use of this therapy in pediatric patients has been described in few cases; [78,79] although recombinant human tissue plasminogen activator (rh-tPA) seems to be an effective therapy for established VOD at a dosage of 0.2 mg m 2 day as an intravenous infusion over 4 hours, further studies are necessary to determine its safety and optimal dosing regimen. Use of ATIII and activated C protein could be a treatment option for VOD; [81,82] ATIII treatment should be further considered in patients with severe VOD, but studies in pediatric series are lacking. Consequently, such a treatment modality is appropriate only in the initial phase of the disease, and is limited by hematologic risk.…”
Section: Treatmentmentioning
confidence: 99%